PERANCANGAN SISTEM DATA WAREHOUSE PEMBELAJARAN PADA PONDOK PESANTREN AL-FURQON - Padeli Padeli; Muhammad Dzulfikar Allam; Nurviani Riska Suharto (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
Al-furqon is foundation of faith-based education that is commonly called the boarding school. Along with the increasing number of students each year the more the teacher or teachers who will take part in the activities of teaching and learning. Thus the more the data that goes into the institution or Pondok Pesantren Al-furqon, these data would need to be stored, processed, and analyzed to produce a useful information for the institution, and reported to the Ministry of Religious Affairs in charge of boarding school. Meanwhile, to make the report, it takes more time to collect information and process data stored in operational databases in the institution. Since it is considered necessary to manage large amounts of data in order to produce an information quickly, then made a design of the data warehouse to facilitate the conduct of data processing, analyzing and reporting the data analysis. The method used the data collection methods, such as observation, interviews, and literature review. After getting the data and then analyzed with the SWOT method, this method describes the shortcomings, strengths and opportunities for improvement in the system. This research resulted in a data warehouse for Al-furqon institution, as well as the amount of storage capacity needed for historical data.